TEACHERS EXPLORE: QUESTIONING SKILLS IN ENGLISH LANGUAGE TEACHING - Saputra, Rizky Imam (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
Effective questioning skills are essential for successful English teaching. Questioning skills are one of the important competencies that English teachers must have to support effective learning. This research took the title "Exploring the Questioning Ability of English Teachers in Grade 9 Uranus EKA TJIPTA KATAYANG Junior High School ". This school is one of the schools located in the interior of oil palm plantations, in Central Borneo. This research has a general problem to be examined, namely how can teachers apply their questioning skills to English subjects in grade 9 Uranus at EKA TJIPTA KATAYANG Junior High School? This study used qualitative research methods. In collecting data, using observation techniques and interviews. The data analysis uses decision-making and verification. With the results obtained, this study shows (1) The ability of teachers to apply basic skills is that the application of basic questioning skills to English teachers in grade 9 Uranus at EKA TJIPTA KATAYANG Junior High School has mostly been carried out well. (2) The ability to ask questions for advanced teachers is still not possible.